Efficacy, safety and single-cell analysis of neoadjuvant immunochemotherapy in locally advanced oral squamous cell carcinoma: a phase II trial - Zhongzheng Xiang; Xiaoyuan Wei; Zhuoyuan Zhang; Yueyang Tang; Linyan Chen; Chenfeng Tan; Yuanyuan Zeng; Jun Wang; Guile Zhao; Zelei Dai; Mingmin He; Ningyue Xu; et al. (Nature Communications)
Abstract The clinical activity of neoadjuvant immunochemotherapy (NAIC) for treating locally advanced oral squamous cell carcinoma (LA-OSCC) remains uncertain. This single-arm, phase II trial (ChiCTR2200066119) tested 2 cycles of NAIC with camrelizumab plus nab-paclitaxel and cisplatin in LA-OSCC patients. For primary endpoint, the major pathological response (MPR) rate was 69.0% (95% confidence interval (CI): 49.2%-84.7%). The treatment was well-tolerated, with only 2 patients (6.45%) having grade 3 or 4 treatment-related adverse events during neoadjuvant treatment. For secondary endpoints, the pathological complete response rate was 41.4% (95%CI: 23.5%-61.1%) and the objective response rate was 82.8% (24/29, 95%CI: 64.2%-94.2%). The 18-month overall survival and disease-free survival probabilities were 96.77% (95%CI: 79.23%-99.54%) and 85.71% (95%CI: 53.95%-96.22%), respectively. Exploratory analysis showed that patients with MPR exhibited higher density of baseline CD4_Tfh_CXCL13 cells, and increased density of tertiary lymphoid structures after NAIC. Baseline CD4_Tfh_CXCL13 cells might be potential predictive biomarker of efficacy. The interaction between CXCL13 on CD4_Tfh_CXCL13 cells and CXCR5 on B cells may play a role in treatment response. These findings suggest the potential of NAIC as a promising treatment for LA-OSCC and offer preliminary insights into responsive biomarkers.